Nursing Program Admission Barriers in the United States: Considerations for Increasing Black Student Enrollment. - Hampton, Michelle DeCoux; Dawkins, Denise DNP, CNL, CHSE; Rickman, Patrick, Sheri DNP, AP FNP-BC; O'Leary-Kelley, Colleen; Onglengco, Raissa; Stobbe, Brenna (Nurse Educator)
Background: The percentage of Black registered nurses (RN) is disproportionate to Black residents in the population, particularly in Southern states. Purpose: This study's purpose was to identify the potential admission barriers for Black students in RN education in the South versus Midwest, Northeast, and West. Methods : A cross-sectional design was used to compare admission criteria for 1597 accredited associate degree in nursing and bachelor of science in nursing programs by geographic region. Results : Southern programs required a significantly higher count of academic metric criteria (multiple grade point average, standardized tests) and nonacademic criteria (proof of health insurance, background checks). Southern programs had a significantly lower count of holistic admissions review criteria (references, essays, volunteer work). Conclusion : Approximately 50% of programs used academic metrics exclusively, and most programs using some holistic criteria assigned greatest weight to academic metrics despite evidence that this disadvantages qualified, underrepresented students. Access to RN education must be improved. Recommendations are discussed for transition to holistic admissions review.